The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.18632/oncotarget.6498
|View full text |Cite
|
Sign up to set email alerts
|

HER2 genomic amplification in circulating tumor DNA from patients with cetuximab-resistant colorectal cancer

Abstract: BackgroundPatients with metastatic colorectal cancer (mCRC) harboring wild-type KRAS benefit from epidermal growth factor receptor (EGFR)-targeted therapy. However, patients who are treated with anti-EGFR antibodies will eventually develop the resistance to those agents. HER2 amplification is one of the mechanisms conferring resistance to anti-EGFR antibody therapy and could therefore be a potential therapeutic target. The aim of this study was to detect HER2 amplification in circulating tumor DNA (ctDNA) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…While ERBB2 amplification and mutation of KRAS, EGFR, and other genes have been identified in ctDNA samples from patients with CRC, this is the first report of an ALK rearrangement in a patient with CRC detected by ctDNA. In this case study, a STRN‐ALK fusion was detected by genomic profiling of ctDNA and later confirmed via tissue testing.…”
Section: Significance Of the Specific Mutation In The Particular Cancermentioning
confidence: 76%
“…While ERBB2 amplification and mutation of KRAS, EGFR, and other genes have been identified in ctDNA samples from patients with CRC, this is the first report of an ALK rearrangement in a patient with CRC detected by ctDNA. In this case study, a STRN‐ALK fusion was detected by genomic profiling of ctDNA and later confirmed via tissue testing.…”
Section: Significance Of the Specific Mutation In The Particular Cancermentioning
confidence: 76%
“…The cut‐off value was defined based on the log2 ratio of the read depth of NGS . We previously reported the detection of copy number gains in HER2 using ddPCR in colorectal cancer patients who were refractory to anti‐EGFR antibody therapy . Thus, ddPCR might have specific features that influence its ability to sensitively detect copy number gains.…”
Section: Discussionmentioning
confidence: 99%
“…20 We previously reported the detection of copy number gains in HER2 using ddPCR in colorectal cancer patients who were refractory to anti-EGFR antibody therapy. 19 mutations are known mechanisms of resistance to EGFR-TKI. 26 In the present study, ERBB4 S341L and EGFR I759M mutations were detected in cfDNA using amplicon sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…After deparaffinization and blocking of endogenous peroxidase, HER2 immunostaining was performed using rabbit anti‐human c‐erbB‐2 primary antibody, diluted 1:100 (Dako Corp., Carpinteria, CA, USA). Primary antibody binding was assessed using the Dako Quick‐Staining, Labeled Streptavidin‐Biotin System (Dako Corp.) and subsequent addition of diaminobenzidine as a chromogen . Scoring was performed according to the clinical practice guideline for breast cancer …”
Section: Methodsmentioning
confidence: 99%